An exploration of information seeking models: Its importance to higher learning institutions / Ramnah Haji Abd. Thani - Abd. Thani, Ramnah (Universiti Teknologi MARA Cawangan Pahang, 2011)
Information searchers with skills and knowledge in information seeking will gather more relevant information than graduates without information skills. Hence, graduates students for instance, need to be excellent in information seeking so as not to be left behind with the overwhelming growth of information. It is believed that there is a need for information users to know and understand how people seek for information as well as, understand the challenges and barriers faced so that they will be able to cope with the environment ahead .